Resurgence of Respiratory Virus after Relaxation of COVID-19 Containment Measures: A Real-World Data Study from a Regional Hospital of Italy. (25th November 2022) - Treggiari, Davide; Piubelli, Chiara; Formenti, Fabio; Silva, Ronaldo; Perandin, Francesca
Abstract : The SARS-CoV-2 virus spread in the Northern Hemisphere during the 2019/2020 influenza seasons and it persisted in the 2021/2022 season. A cocirculation of SARS-CoV-2 and influenza viruses was expected in Italy during the winter seasons. This study aims to investigate the prevalence of influenza and respiratory syncytial viruses observed in a hospital in Verona Province, Italy hospital during these past three winter seasons and to compare our data with national and global surveillance reports on the transmission of respiratory viruses in the preceding decade. Our findings clearly demonstrated the extremely low prevalence of influenza virus among hospitalized patients and outpatients during the first two COVID-19 winter seasons, with a reemergence of respiratory syncytial virus in the late 2021. Containment measures may have played an important role in temporarily stopping the circulation of respiratory viruses, but after relaxation, in 2021, we experienced an unusual increase of respiratory syncytial viruses at the beginning of the winter season.